Cation exchange characteristics of some soil from the State of São Paulo - Pratt, Parker F.; Alvahydo, Roberto (Pesquisa Agropecuaria Brasileira, 2024)
The permanent and pH-dependent cation-exchange capacity (CEC), exchangeable cations, exchange acidity, base saturation, CaCO3, titration curves, and clay mineralogy were determined for soils classified as Red-Yellow Podzols, Red-Yellow Latosols, and “Roxo” Latosols (Terra Roxa). The Podzols contained the highest amounts of KCl acidity and permanent CEC. The ratio of pH-dependent to permanent CEC was lowest for Podzols and highest for the "Roxo" Latosols. Titration curves obtained for "Roxo" Latossols were distinctly different from those for Podzols. The "Roxo" Latosols had only small quantities of crystalline clay minerals where as all of the Podzols had kaolinites. Those podzols with high permanent CEC (approximately 8 mE per 100 g) contained detectable amounts of 2:1 clays. The data show that accumulation of KCl acidity (assumed to be exchangeable Al) is dependent on the content of 2:1 type clay minerals.